Improve on research, varsities told - Aziz, Hazlina (New Strait Times, 2017)
MALAYSIA'S universities have to improve the quality of research if they want to improve their standings in the Times Higher Education (THE) rankings in future years according to THE rankings editor Phil Baty in a statement announcing THE's inaugural Asia-Pacific (APACI University Rankings last week.